Strategi Mengomunikasikan Injil kepada Generasi Mileneal - Wijiati, Maria (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2020)
The church is a means of proclaiming the kingdom of God on earth; as a representation of God's kingdom who is present in this world to witness God's work and plan in human history. In order to work on its calling to reach the world and disciple people, the church needs an approach or a way to do it. The right approach will help the church or believers to be more effective in communicating the gospel to the world, including the millennial generation. This article aims to show an effective and strategic approach in communicating the gospel to millennial generations. This research is qualitative research with a literature approach that uses descriptive methods. In conclusion, the church needs to have a digital communication strategy using various social media as a strategy to communicate the gospel to the millennial generation. Abstrak Gereja adalah alat untuk menyatakan kerajaan Allah di muka bumi; sebagai representasi kerajaan Allah yang hadir dalam dunia ini untuk menyaksikan karya dan rencana Allah dalam sejarah umat manusia. Untuk dapat mengerjakan panggilannya dalam menjangkau dunia dan memuridkan orang-orang, gereja membutuhkan pendekatan atau cara untuk melakukannya. Pendekatan yang tepat akan menolong gereja atau orang percaya untuk lebih efektif dalam mengomunikasikan Injil kepada dunia, termasuk kepada generasi milenial. Artikel ini bertujuan untuk menunjukkan pendekatan yang efektif dan strategis dalam mengomunikasikan Injil kepada generasi milenial. Penelitian ini merupakan penelitian kualitatif dengan pendekatan literatur yang menggunakan metode deskriptif. Kesimpulannya, gereja perlu memiliki strategi komunikasi digital dengan penggunaan berbagai media sosial sebagai strategi mengomunikasikan Injil kepada generasi milenial.